Mouth, soul and heart: vision and corporeality within a constellation of religious images (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This essay aims to add further tension to the role of images in relation to religious experience, affirming that every sacred gaze is a haptic gaze, which is to say, a particular way of engaging with images through corporeality, proximity and touching in a non hierarchical way. The proposals exposed here are based on critical visual methodologies and it unfolds from a constellation of images emphasizing certain body parts in a religious sense, highlighting some of their elements, such as the soul, the mouth and the heart. These images are put in relation to other images, objects and prayers, and are organised in thematic series following their function on the corporal focus. The selected images comprise a series of Santa Rosa de Lima’s deathbed, then the attention goes to the exposed wounds of some saints devoted to the Sacred Heart of Jesus, and it ends in a group of iconographies where hearts are depicted independently of the body.
Keywords: Religious visual culture; corporeality; haptic visuality; sacred gaze